Blood pressure control and risk of post-stroke dementia among the elderly: A population-based screening study - Wu, Hao; Ren, Zhihong; Gan, Jinghuan; Lü, Yang; Niu, Jianping; Meng, Xinling; Cai, Pan; Li, Yang; Gang, Baozhi; You, Yong; Lv, Yan; Liu, Shuai; et al. (Frontiers in Neurology, 2022)
Background Post-stroke dementia (PSD) has adverse effects on the quality of work and life in elderly stroke survivors. There are inconsistent results on the impacts of blood pressure control on the risk of PSD in people aged 65 years and above. Objective This study was performed to explore whether poorly-controlled blood pressure was associated with an increasing risk of PSD. Methods The study population was enrolled from cross-sectional research conducted in 106 communities of rural northern China. In Phase I, a total of 7,448 people aged ≥65 years, including 830 with stroke history, completed a questionnaire, a physical examination, and a cognitive assessment. Phase II further confirmed the diagnosis of PSD. Well-controlled blood pressure was defined as an average systolic blood pressure of <140 mmHg and average diastolic blood pressure of <90 mmHg over two readings in person. Failure to meet these criteria was considered as poorly-controlled blood pressure. Results The crude prevalence rate of PSD among stroke survivors aged 65 years and over was 17.8% [95% confidence interval (CI) 15.2–20.4%]. Among the 830 stroke survivors, the proportions of PSD gradually increased with age and the crude prevalence rates for PSD were 10.2% (95% CI 5.6–14.9%), 14.8% (95% CI 10.1–19.5%), 18.8% (95% CI 14.1–23.5%), and 27.4% (95% CI 20.8–34.1%) in subjects aged 65–69, 70–74, 75–79 and ≥80 years, respectively. Participants in the poorly-controlled blood pressure group were more likely to suffer from PSD (28.4 vs.15.3%, P < 0.001), be older (75.81 ± 4.97 vs. 74.74 ± 5.83, P < 0.05), and have a worse cognitive level (22.26 ± 7.05 vs. 24.10 ± 6.02, P < 0.05). Compared with well-controlled blood pressure patients, poorly-controlled blood pressure in stroke survivors significantly increased risk of PSD (odds ratio = 2.20, 95% CI 1.45–3.32) after adjusting for age, gender, and education. Conclusions The crude prevalence of PSD among stroke survivors aged ≥65 years was 17.8% at community level. In addition to lower education level and older age, poorly-controlled blood pressure was also an independent risk factor for PSD among the elderly, which is amenable to intervention. Therefore, it is essential to control blood pressure to reduce PSD incidence.